Brain dynamics and motor behavior: A case for efficiency and refinement for superior performance - Hatfield, B. D. (Kinesiology Review, 2018)
The paper presents a theoretical perspective on brain activity that characterizes expert cognitive-motor performance grounded in neural and psychomotor efficiency. Evidence for the position is derived from several different measurement tools (EEG, ERPs, fMRI, EEG coherence) based on empirical studies of (1) expert-novice contrasts, (2) changes in the brain after practice, and (3) motor performance under conditions of mental stress. The impact of mental stress on brain processes during motor performance is then discussed followed by a model of the hypothesized central neural responses to emotion-eliciting events to explain resilience to stress and the ability to "perform under pressure" as observed in high-performing athletes. An overall explanation is offered of the cascade of events that link the perception of the environment in which the performance occurs to the peripheral process of motor unit recruitment and the resultant quality of movement. This integrative perspective on human performance considers multiple levels of explanation including the psychology of sport performance, cognitive-motor neuroscience, and basic biomechanics to understand the kinematic qualities of movement and the effort cost involved.